Pelatihan Kebersyukuran dalam Meningkatkan Kesehatan Mental pada Ibu-Ibu Majelis Taklim di Kota Pekanbaru - Liliza Agustin; Vivik Shoviah; Yulita Kurniawati (Lembaga penelitian dan pengabdian kepada masyrakat, 2020)
Community service is based on research and method development. Against the backdrop of the effort to give birth to Islamic psychological interventions, the researcher tried to design a gratefulness training module. The gratefulness training model is a theistic psychological intervention which is the development of a training model taken from the concept of gratitude by Ibn Qayyim Aljauziyah. What distinguishes it is the conceptualization and emphasis of intervention in several ways. The method development is combining the concept of Gratitude with gratefulness in a training forum as a psychological intervention. The hope is that gratefulness training can be applied, conducted research, and can be considered as a single intervention or additional intervention, especially for Muslims. The participants of the gratefulness training were 20 people in the Taklim Council in Pekanbaru City.